2013
DOI: 10.1002/art.37937
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Analysis of Interleukin–23– and Interleukin‐12–Positive Cells in the Spine of Patients With Ankylosing Spondylitis

Abstract: Objective. The interleukin-12 (IL-12) family of cytokines has been suggested to play a critical role in inflammatory autoimmune diseases, and recent studies analyzing peripheral blood and synovial fluid from patients with spondyloarthritides suggest that IL-23 might be a proinflammatory factor in these disorders. This study was undertaken to investigate the presence and source of IL-23 in the spines of patients with ankylosing spondylitis (AS).Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 35 publications
1
82
0
5
Order By: Relevance
“…Infection also stimulates the up-regulation of T cells to maintain immune homeostasis [4]. There are increasing findings suggesting the involvement of T cells in AS [5,6]. Recent studies reveal that disordered T cells are observed in peripheral blood and inflammatory joints from patients with AS [7,8].…”
Section: Introductionmentioning
confidence: 97%
“…Infection also stimulates the up-regulation of T cells to maintain immune homeostasis [4]. There are increasing findings suggesting the involvement of T cells in AS [5,6]. Recent studies reveal that disordered T cells are observed in peripheral blood and inflammatory joints from patients with AS [7,8].…”
Section: Introductionmentioning
confidence: 97%
“…Although IL-23 serum levels (14,(40)(41)(42) and IL-23 expression in the subchondral bone marrow from the facet joints (26) are up-regulated in AS patients, no correlation has been found with MRI inflammation or clinical DA (24). As IL-17 and IL-23 levels fall significantly in responders to anti-TNFα drugs and rise in non-responders (41), both cytokines (IL-17, IL-23) are considered promising therapeutic targets (42,43). In addition, IL-22 interconnected with IL-17 and Th17 cells is elevated in patients with AS (43).…”
Section: Original Papermentioning
confidence: 99%
“…As IL-17 and IL-23 levels fall significantly in responders to anti-TNFα drugs and rise in non-responders (41), both cytokines (IL-17, IL-23) are considered promising therapeutic targets (42,43). In addition, IL-22 interconnected with IL-17 and Th17 cells is elevated in patients with AS (43). When IL-17, IL-22 and IL-23 were examined in our patients, they were found to be below detection levels in all three patient cohorts.…”
Section: Original Papermentioning
confidence: 99%
“…Synovial fluid in patients with SpA shows elevated concentration of IL-23 [23]. High expression of this cytokine has also been found in vertebral facet joints, where the cytokine is produced by macrophages residing in fibrous tissue and neutrophils, macrophages, and dendritic cells found in subchondral bone marrow [24].…”
Section: Cytokine Involvement In Arthritismentioning
confidence: 99%